(untitled) (Acta Judicial Journal, 2018)
The referred Court Order addresses the problem of legal standing of the plaintiff on foreclosure, when the mortgage loan that is executed was already securitised The order stablish that by means of the securitization the assignment of receivable takes place, so the rightholder start to be the securitization fund. The fund owner of the mortgage loan, prior to the exercise of the mortgage action must have the registration of title in the Land Registry, especially when after 2015 law reforms it is possible this type of registration.